2015
DOI: 10.1016/j.jnoncrysol.2015.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity, crack initiation and defect resistance in alkali-borosilicate glasses: From normal to anomalous behavior

Abstract: We provide a comprehensive description of the defect tolerance of sodium-borosilicate glasses upon sharp contact loading. This is motivated by the key role which is taken by this particular glass system in a wide variety of applications, ranging from electronic substrates, display covers and substrates for biomedical imaging and sensing to, e.g., radioactive waste vitrification. The present report covers the mechanical properties of glasses in the Na 2 O-B 2 O 3 -SiO 2 ternary over the broad range of compositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
156
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(168 citation statements)
references
References 135 publications
(265 reference statements)
10
156
2
Order By: Relevance
“…It provides different analysis parameters: Usually, hardness is determined using the Oliver-Pharr technique Pharr, 1992, 2004) and is given by: Malchow et al (2015). b Taken from the study by Limbach et al (2015). c Determined by ultrasonic echography.…”
Section: Mechanical Testing Of Glassmentioning
confidence: 99%
See 2 more Smart Citations
“…It provides different analysis parameters: Usually, hardness is determined using the Oliver-Pharr technique Pharr, 1992, 2004) and is given by: Malchow et al (2015). b Taken from the study by Limbach et al (2015). c Determined by ultrasonic echography.…”
Section: Mechanical Testing Of Glassmentioning
confidence: 99%
“…An echometer (model 1077, Karl Deutsch GmbH) working with an accuracy of ±1 ns was employed. More information on ultrasonic measurements and how elastic properties such as shear modulus G, bulk modulus K, and Young's modulus E, and Poisson ratio ν can be found elsewhere (Limbach et al 2015;Möncke et al, 2016).…”
Section: General Glass Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to understand these cracking behaviour of various glasses, several physical parameters, such as the density, Poisson's ratios and the coordination of boron in the glass have been correlated with the cracking behaviour. (10)(11)(12)(13)(14) It is well known that phase structures influence certain physical and chemical properties of glasses. (15)(16)(17) It has been reported that the fracture toughness of glasses is influenced by the phase separated structure.…”
Section: Introductionmentioning
confidence: 99%
“…In the sodium-borosilicate ternary system, glasses that preferred compaction under an indenter showed higher crack resistance [24]. The deformation behavior, shear-driven or densification-driven, was affected by the incorporation of SiO 2 and/ or B 2 O 3 and the ratio of Na 2 O/B 2 O 3 [25].…”
Section: Discussionmentioning
confidence: 99%